Using human induced pluripotent stem cells to investigate the roles of astrocytes in spinal muscular atrophy - Loh, Sharon Jia Hui (2018)
Spinal muscular atrophy (SMA) is a neuromuscular disease caused by the mutation of SMN1 gene and which is characterized by the selective degeneration of lower motor neurons. Through the years, it has become more evident that SMA is not solely a disease of the lower motor neurons, but other cell types within and outside the brain were also found to be dysfunctional. The non-cell autonomous roles of astrocytes in influencing neuronal survival in neurodegenerative diseases is an emerging concept and has only been well-described in ALS. Till date, the involvement of astrocytes, which make up the majority of the cell population in the CNS, is still poorly understood in SMA. In this thesis, WT and SMA human iPSC-derived astrocytes and motor neurons were generated with high efficiencies and were used as a paradigm to investigate underlying dysregulated molecular pathways in SMA astrocytes and to uncover aberrant interactions between SMA motor neurons and astrocytes. Global gene expression profiling revealed that SMA astrocytes were hyper-reactive based on their upregulated expression of genes involved in ECM remodeling (MMP9 and MMP13) and inflammation (IL32 and CXCL6). Functional characterizations showed that SMA astrocytes were incapable of eliciting calcium signaling and taking up extracellular glutamate, suggesting ineffective synaptic transmissions and induction of neuronal excitotoxicity respectively. Coculture experiments indicated that SMA astrocytes augmented their reactivity upon exposure to WT and SMA motor neurons and produced elevated levels of MMP9. The increase in astrocytic reactivity and net secretory MMP9 levels in SMA astrocytes cocultures correlated with motor neuronal demise. Collectively, results obtained in this research show that SMA astrocytes are defective and play important roles in influencing motor neuron survivability in SMA.